Nearpod-Based Interactive Multimedia to Improve Students' Critical Thinking on Human Respiratory System: Multimedia Interaktif Berbasis Nearpod untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi Sistem Pernapasan Manusia - Rohimah, Iim; Arifin, M. Zainal; Windiyani, Tustiyana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The integration of technology in elementary education remains uneven, particularly in fostering higher-order thinking skills. Specific Background: At SDN Cimahpar 1 in Bogor City, fifth-grade students exhibited low critical thinking performance, with learning media not fully leveraging digital interactivity. Knowledge Gap: While digital tools like Nearpod offer promising potential, empirical evidence on their efficacy in elementary science education, especially on topics like the human respiratory system, is limited. Aims: This study aimed to develop and validate an interactive multimedia product based on Nearpod to enhance critical thinking skills in science. Results: Employing the ADDIE model within a Research and Development (R&D) framework, the media was tested on 28 students through a one-group pretest-posttest design. Validation scores from media, content, and language experts ranged from 82.86% to 95.71% (